Globalization and Pandemic: lessons and perspectives - LUQUEZ, JULIANA (Geografares, 2021)
This is a remote interview given by Paul Claval, professor emeritus at the University of Paris Sorbonne IV, in July 2020. This interview marked the end of the 1st Cycle of Remote Interviews promoted by the research group Dinâmicas Territoriais e Espaços Fronteiriços (DITEFRON), within the Geography Course of the Universidade Estadual de Mato Grosso do Sul (UEMS/Campus Jardim).